Mediterranean and Western diet effects on Alzheimer's disease biomarkers, cerebral perfusion, and cognition in mid‐life: A randomized trial. Issue 3 (26th July 2021) - Hoscheidt, Siobhan; Sanderlin, Ashley H.; Baker, Laura D.; Jung, Youngkyoo; Lockhart, Samuel; Kellar, Derek; Whitlow, Christopher T.; Hanson, Angela J.; Friedman, Seth; Register, Thomas; Leverenz, James B.; Craft, Suzanne
Abstract: Introduction: Mid‐life dietary patterns are associated with Alzheimer's disease (AD) risk, although few controlled trials have been conducted. Methods: Eighty‐seven participants (age range: 45 to 65) with normal cognition (NC, n = 56) or mild cognitive impairment (MCI, n = 31) received isocaloric diets high or low in saturated fat, glycemic index, and sodium (Western‐like/West‐diet vs. Mediterranean‐like/Med‐diet) for 4 weeks. Diet effects on cerebrospinal fluid (CSF) biomarkers, cognition, and cerebral perfusion were assessed to determine whether responses differed by cognitive status. Results: CSF amyloid beta (Aβ)42/40 ratios increased following the Med‐diet, and decreased after West‐diet for NC adults, whereas the MCI group showed the reverse pattern. For the MCI group, the West‐diet reduced and the Med‐diet increased total tau (t‐tau), whereas CSF Aβ42 /t‐tau ratios increased following the West‐diet and decreased following the Med‐diet. For NC participants, the Med‐diet increased and the West‐diet decreased cerebral perfusion. Discussion: Diet response during middle age may highlight early pathophysiological processes that increase AD risk.